1999
DOI: 10.2169/internalmedicine.38.988
|View full text |Cite
|
Sign up to set email alerts
|

Cavernous Sinus Syndrome Associated with Nonsecretory Myeloma.

Abstract: The case of a 53-year-old manwho developed cavernous sinus syndrome (CSS) four years after being diagnosed as having nonsecretory myeloma is described. He was admitted with diplopia and dull pain over the right infraorbital and zygomatic region in June 1997. The cause of CSS was the intracranial involvement of myeloma, which was diagnosed by fiberscopic biopsy. The results of endocrinologic evaluation were almost normal. The response to radiotherapy and chemotherapy was mild. CSS caused by nonsecretory myeloma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
4
0
1
Order By: Relevance
“…Santral sinir sistemi miyeloması; lokalize parankimal formlarda olabileceği gibi, leptomeninks veya kraniyal sinir tutulumu şeklinde de karşımıza çıkabilir (9). Kavernöz sinüs tutulumu ise çok nadir bildirilmiştir ve kötü prognozla birliktedir (7,11,12). Radyolojik olarak doğrulanması gereklidir (6,7).…”
Section: Discussionunclassified
“…Santral sinir sistemi miyeloması; lokalize parankimal formlarda olabileceği gibi, leptomeninks veya kraniyal sinir tutulumu şeklinde de karşımıza çıkabilir (9). Kavernöz sinüs tutulumu ise çok nadir bildirilmiştir ve kötü prognozla birliktedir (7,11,12). Radyolojik olarak doğrulanması gereklidir (6,7).…”
Section: Discussionunclassified
“…Multiple cranial neuropathies in combination such as Foster Kennedy syndrome, cavernous sinus syndrome, Gradenigo syndrome and jugular foramen syndrome had been reported in late stages of MM. [3][4][5] Multiple CNs involvements as the initial presentation for plasmacytoma had been reported very rarely only. [6][7][8]11] Ko et al [6] reported a case of the intracranial plasmacytoma in the cavernous sinus presented as left IV and partial V CN palsy.…”
Section: Discussionmentioning
confidence: 99%
“…[2] Multiple cranial neuropathies had been reported in late stages of MM. [3][4][5] Very rarely multiple cranial nerves (CN) involvement by plasmacytoma may be presenting feature of MM. [6][7][8] Here, we report a case of multiple CN palsy (right 3 rd , 6 th , 9 th , 10 th and 12 th CNs) as first presentation of the intracranial plasmacytoma.…”
Section: Introductionmentioning
confidence: 99%
“…The multiple cranial neuropathies in combination such as Foster Kennedy syndrome, cavernous sinus syndrome, Gradenigo syndrome and jugular foramen syndrome had been reported in late stages of MM. [6,7,8] Multiple CNs involvements as the initial presentation for plasmacytoma had been reported very rarely. [3,4,5] Ko et al reported a case of the intracranial plasmacytoma in the cavernous sinus presented as left 6th and partial 5 th CN palsy.…”
Section: Case Reportmentioning
confidence: 99%